Pengaruh Dewan Komisaris, Komite Audit, Dan Dewan Pengawas Syariah Terhadap Kinerja Perbankan Syariah - Jumainii Azizah; Erinos NR (Universitas Negeri Padang, 2020)
This study aims to determine and analyze the influence of the Board of Commissioners, the Audit Committee and the Sharia Supervisory Board on the Performance of Sharia commercial banks Empirical studies on Sharia commercial banks in 2014-2018 both simultaneously and in part. The data analysis method used is panel data regression analysis. Using a purposive sampling method to get a sample of 10 Islamic banks from 12 Islamic banks. Based on the results of the study note that the board of commissioners, audit committees, sharia supervisory boards simultaneously affect the performance of Islamic banks. But partially, the board of commissioners, audit committee, sharia supervisory board did not affect the performance of Islamic Banks in Islamic Banking in 2014-2018.